Evaluating the business value of website performance - Čegan, Lukáš (My University, 2016)
This paper provides an overview of how to measure real web user performance characteristics as well as monitor real web user behavior, and how this measured data is converted into the business value of a website. Evaluating the business value is realized by a proposed system which is composed of two levels. The first level of the system is formed by a monitor framework which logs all network performance parameters, environment settings and also catches user interaction such as mouse movement, page scrolling or activation elements of a page. The second level is formed by business analytic tools which help us to discover a links between business values and website environment entities. Discovering is based on measured data from the first level and properly established metrics. Results of the analysis make it possible for business-value driven website changes and optimizations.
Vyhodnocení obchodní hodnoty výkonu webové stránky
Keywords: business value; real user monitoring; web performance; evaluation; byznys hodnota: monitoring reálných uživatelů: výkon webu; ohodnocení